Rancang Bangun Aplikasi Pengelolaan Nilai Rapor Pada SMA Muhammadiyah 2 Sidoarjo - Anugerah, Tito Jiwa; Wibowo, Januar; Ayuningtyas, Ayuningtyas (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Muhammadiyah 2  Senior High School Sidoarjo is one of the schools who need computerized information systems to be able to simplify the process of managing the students values. Problem in implementing the assessment process is entering data of students values. Sometimes have errors that makes teachers or the academic must change those values manually and then replace it with new data.The process of making this system starting from analyzing the current system. The results of the analysis is converted into 'document flow' which is divided based on based on the processes of existing transactions. From these 'document flow' improved be a new system which written into the ' flow system '.The implementation of these application to report cards of students values at  Muhammadiyah 2 Senior high school Sidoarjo, it is expected to reduce recording errors recording that may occur in the management students values in Muhammadiyah 2 Senior high school Sidoarjo. This system is also expected to further accelerate the reporting process that can be used by the decision-makers to further improve the performance and service there.